Decreased Implantation Number after in Utero Artificial Insemination Can Reflect an Impairment of Fertility in Adult Male Rats after Exogenous Leptin Exposure - Fernandez, Carla D. B. [UNESP]; Fernandes, Glaura S. A. [UNESP]; Favareto, Ana Paula A. [UNESP]; Perobelli, Juliana E. [UNESP]; Sanabria, Marciana [UNESP]; Kempinas, Wilma D. G. [UNESP] (Springer Nature, 2017)
Leptin is a protein secreted by the adipocytes, which serves as a link between fat and brain. Its main action is to decrease appetite and increase energy expenditure, but it is also involved in the control of different neuroendocrine systems, including gonadal axis. Although the effects of leptin deficiency on reproduction are well recognized, the effect of excess leptin on male reproductive function is not clear. The aim of this study was to evaluate fertility and sperm parameters of male rats exposed to exogenous leptin. A group of adult male rats received exogenous leptin intraperitoneally (30 μg/kg/day) for 42 days, and a control group received only the vehicle during the same period. After the treatment, animals were evaluated for sperm count, sperm motility, and fertility after intrauterine artificial insemination. There was no statistically significant difference between the groups related to sperm production, sperm concentration, and sperm motility. However, fertility evaluation after artificial insemination showed a quantitative decrease in the uterus plus fetuses weight, number of implantation sites, and number of live fetuses. The fertility potential showed a reduction of about 40%, whereas the preimplantation loss rate increased more than 2-fold in leptin-treated animals. In conclusion, leptin administration to nonobese male rats impairs ability of treated animals to generate offspring, since the occurrence of implantation was diminished. So leptin can impair sperm quality, affecting the reproductive capacity.
Keywords: fertility; implantation rate; leptin; male reproduction.